Interoception, cardiac health, and heart failure: The potential for artificial intelligence (AI)—driven diagnosis and treatment - Mahavir Singh; Anmol Babbarwal; Sathnur Pushpakumar; Suresh C. Tyagi (Physiological Reports)
Abstract “I see, I forget, I read aloud, I remember, and when I do read purposefully by writing it, I do not forget it.” This phenomenon is known as “interoception” and refers to the sensing and interpretation of internal body signals, allowing the brain to communicate with various body systems. Dysfunction in interoception is associated with cardiovascular disorders. We delve into the concept of interoception and its impact on heart failure (HF) by reviewing and exploring neural mechanisms underlying interoceptive processing. Furthermore, we review the potential of artificial intelligence (AI) in diagnosis, biomarker development, and HF treatment. In the context of HF, AI algorithms can analyze and interpret complex interoceptive data, providing valuable insights for diagnosis and treatment. These algorithms can identify patterns of disease markers that can contribute to early detection and diagnosis, enabling timely intervention and improved outcomes. These biomarkers hold significant potential in improving the precision/efficacy of HF. Additionally, AI‐powered technologies offer promising avenues for treatment. By leveraging patient data, AI can personalize therapeutic interventions. AI‐driven technologies such as remote monitoring devices and wearable sensors enable the monitoring of patients' health. By harnessing the power of AI, we should aim to advance the diagnosis and treatment strategies for HF. This review explores the potential of AI in diagnosing, developing biomarkers, and managing HF.